Laboratory blood analysis in Strigiformes—Part I: hematologic reference intervals and agreement between manual blood cell counting techniques. (27th January 2015) - Ammersbach, Mélanie; Beaufrère, Hugues; Gionet Rollick, Annick; Tully, Thomas
<x xml:space="preserve">Abstract</x> Background While hematologic reference intervals (RI) are available for multiple raptorial species of the order Accipitriformes and Falconiformes, there is a lack of valuable hematologic information in Strigiformes that can be used for diagnostic and health monitoring purposes. Objectives The objective was to report RI in Strigiformes for hematologic variables and to assess agreement between manual cell counting techniques. Methods A multi‐center prospective study was designed to assess hematologic RI and blood cell morphology in owl species. Samples were collected from individuals representing 13 Strigiformes species, including Great Horned Owl, Snowy Owl, Eurasian Eagle Owl, Barred Owl, Great Gray Owl, Ural Owl, Northern Saw‐Whet Owls, Northern Hawk Owl, Spectacled Owl, Barn Owl, Eastern Screech Owl, Long‐Eared Owl, and Short‐Eared Owl. Red blood cell count was determined manually using a hemocytometer. White blood cell count was determined using 3 manual counting techniques: (1) phloxine B technique, (2) Natt and Herrick technique, and (3) estimation from the smear. Differential counts and blood cell morphology were determined on smears. Reference intervals were determined and agreement between methods was calculated. Results Important species‐specific differences were observed in blood cell counts and granulocyte morphology. Differences in WBC count between species did not appear to be predictable based on phylogenetic relationships. Overall, most boreal owl species exhibited a lower WBC count than other species. Important disagreements were found between different manual WBC counting techniques. Conclusions Disagreements observed between manual counting techniques suggest that technique‐specific RI should be used in Strigiformes.